Fast Out‐of‐Core Octree Generation for Massive Point Clouds. (24th November 2020) - Schütz, Markus; Ohrhallinger, Stefan; Wimmer, Michael
Abstract: We propose an efficient out‐of‐core octree generation method for arbitrarily large point clouds. It utilizes a hierarchical counting sort to quickly split the point cloud into small chunks, which are then processed in parallel. Levels of detail are generated by subsampling the full data set bottom up using one of multiple exchangeable sampling strategies. We introduce a fast hierarchical approximate blue‐noise strategy and compare it to a uniform random sampling strategy. The throughput, including out‐of‐core access to disk, generating the octree, and writing the final result to disk, is about an order of magnitude faster than the state of the art, and reaches up to around 6 million points per second for the blue‐noise approach and up to around 9 million points per second for the uniform random approach on modern SSDs.